Anti-SARS-CoV-2 Seropositivity Among Medical Students in Copenhagen. (19th August 2021) - Madsen, Johannes R; Nielsen, Jacob P S; Fogh, Kamille; Hansen, Cecilie B; Nielsen, Pernille B; Lange, Theis; Hasselbalch, Rasmus B; Garred, Peter; Iversen, Kasper
Abstract: Background: Health care workers are at a higher risk of getting infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) than the general population. Knowledge about medical students' exposure to SARS-CoV-2 is lacking. Thus, we measured the prevalence of SARS-CoV-2 antibodies in a cohort of Danish medical students. Methods: We invited all medical students at the University of Copenhagen (UCPH) to participate. Students underwent venous blood sampling and a questionnaire about work-life behaviors possibly associated with SARS-CoV-2 exposure and coronavirus disease 2019 (COVID-19) symptoms. Samples were analyzed for total immunoglobulin G (IgG) antibodies against SARS-CoV-2, and seropositive samples were screened for IgG, immunoglobulin M, and immunoglobulin A antibodies. We determined associations between seropositivity and clinical and social activities and self-reported symptoms. Results: Between October 19 and 26, 1120 students participated in the questionnaire and 1096 were included. Of all included, 379 (34.58%) were seropositive. Seropositivity was associated with attendance at 2 parties at UCPH, on February 29 and March 6, 2020 (odds ratio [OR], 5.96; 95% CI, 4.34–8.24; P < .001). Four hundred sixty-one students (42.06%) worked with COVID-19 patients, which was significantly associated with seropositivity (OR, 1.38; 95% CI, 1.03–1.85; P = .033). The symptom most associated with seropositivity was loss of smell and/or taste (n = 183 of all, 31.35%; OR, 24.48; 95% CI, 15.49–40.60; P < .001). Bachelor's students were significantly more likely to be seropositive than Master's students (42.28% vs 16.87%; P < .001). Conclusions: Medical students have the highest reported seropositivity in the Danish health care system. In this cohort of students at UCPH, seropositivity was associated with social behavior markers and, to a lesser extent, with self-reported contact with SARS-CoV-2-infected patients.